Long‐Term Effects of Glucosamine and Chondroitin Sulfate on the Progression of Structural Changes in Knee Osteoarthritis: Six‐Year Followup Data From the Osteoarthritis Initiative. Issue 10 (16th September 2016) - Raynauld, Jean‐Pierre; Pelletier, Jean‐Pierre; Abram, François; Dodin, Pierre; Delorme, Philippe; Martel‐Pelletier, Johanne
Abstract : Objective: To examine the long‐term (6‐year) effect of combined glucosamine (Glu) and chondroitin sulfate (CS) treatment on cartilage volume in knee osteoarthritis (OA). Methods: Participants were from the Osteoarthritis Initiative progression and incidence subcohorts, had magnetic resonance imaging (MRI) of the target knee at baseline and 6 years, joint space width >1 mm, and data available on Glu/CS consumption (n = 1, 593). They were stratified into 2 main groups based on whether or not they had medial meniscal extrusion at baseline. The group with meniscal extrusion (n = 429) was further stratified into subgroups based on exposure or no exposure to Glu/CS as follows: not exposed, 1 year, 2–3 years, and 4–6 years. Cartilage volume was assessed using fully automated quantitative MRI technology. Results: The Jonckheere‐Terpstra trend test indicated that treatment with Glu/CS significantly reduced the cartilage volume loss in the global knee, associated with the lateral compartment. Multivariate analysis further demonstrated that the extent of the treatment's positive effect was related to exposure time to treatment, the protective effect at 6 years being significant in participants exposed to ≥2 years of treatment. Conclusion: These findings provide future support for the long‐term protective structure‐modifying effects of Glu/CS treatment in knee OA subjects.